Status of operations of the professional regulation commission : an evaluation year 1996-1997 - Perez, Gliceria R. (Manila : National University, 1997)
The PRC is an agency of the National Government charged with the regulation and licensing professions in the Philippines except the law profession.
Chapter 1. The problem and its background -- Chapter 2. Review of Related Literature and Studies -- Chapter 3. Research Design and Methodology -- Chapter 4. Presentation, analysis and Interpretation of Data -- Chapter 5. Summary, Conclusions and Recommendations.
Researcher-made instrument was used in the study.
Includes bibliographical references.